(untitled) (Ameghiniana, 2017)
Eleven new records of marine gastropods from several localities in west-central Argentina are hereby presented, including the following new species: Proconulus kotrus, Calliotropis (Riselloidea) ligosta, Lyosoma truquicoensis, Exelissa crassicostata, Cirsocerithium agriorivensis, Cataldia? binodosa, Vanikoropsis? leviplicata and Tornatellaea neuquina. These records were recovered from two Early Cretaceous units of the Neuquén Basin, the Mulichinco (Valanginian) and the Agrio (upper Valanginian–upper Hauterivian/lowermost Barremian) formations. The families Proconulidae, Calliotropidae, Neritidae, Cryptaulacidae, ?Pseudomelaniidae, Vanikoridae, Epitoniidae and Acteonidae are represented whilst one record is yet to be assigned at the family level. Resumen. NUEVOS REGISTROS DE GASTRÓPODOS MARINOS DEL CRETÁCICO INFERIOR DEL CENTRO-OESTE DE ARGENTINA. Se dan a conocer 11 nuevos registros de gastrópodos marinos procedentes de numerosas localidades en el centro-oeste de Argentina. Entre ellos se encuentran las siguientes especies nuevas: Proconulus kotrus, Calliotropis (Riselloidea) ligosta, Lyosoma truquicoensis, Exelissa crassicostata, Cirsocerithium agriorivensis, Cataldia? binodosa, Vanikoropsis? leviplicata y Tornatellaea neuquina. Estos registros proceden de dos unidades de edad cretácica temprana de la Cuenca Neuquina: las formaciones Mulichinco (Valanginiano) y Agrio (Valanginiano superior–Hauteriviano superior/Barremiano basal). En esta fauna se encuentran representadas las familias Proconulidae, Calliotropidae, Neritidae, Cryptaulacidae, ?Pseudomelaniidae, Vanikoridae, Epitoniidae y Acteonidae, con un registro no asignado aún a nivel familia.